EFFECT OF GENDER DIFFERENCES ON THE EFFICACY AND SAFETY OF REPERFUSION THERAPY OF ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION (DATA OF RETROSPECTIVE SINGLE-CENTER STUDY - HOSPITAL PERIOD) - D. B. Nemik; G. V. Matyushin; A. V. Protopopov; A. V. Shulmin; S. A. Ustyugov (Столичная издательская компания, 2016)
Gender differences can significantly affect mortality in ST-segment elevation myocardial infarction (STEMI) in real practice. Aim. To evaluate the effect of gender on mortality in STEMI. Material and methods. Outcomes of in-hospital stage of treatment of 553 men (67.7%) and 263 women (32.3%) were analyzed in single-center retrospective study. Primary percutaneous coronary intervention (pPCI) and pharmacoinvasive strategy (PIS) were used in 160 (60.8%) and 103 (39.2%) women, respectively, as well as in 295 (53.3%) and 258 (46.7%) men, respectively. Patients with time "primary medical contact (PMC) - balloon" less than 60 min and "symptom - PMC" more than 6 hours were excluded. The majority of patients were in a time interval "PMC - balloon" about 120 minutes. Results. Mortality in women was significantly higher than this in men regardless of the reperfusion strategy - 15.3% in whole (18.1% at pPCI and 10.9% at PIS), and 3.1% in whole (5.1% at pPCI and 0.8% at FIS), respectively (p<0.001). The probability of lethal outcome in women was 4 times higher than this in men (odds ratio 4.4; 95% confidence interval 2.7-7.1). Conclusion. Clinical characteristics of the patients due to gender differences make a significant contribution to the course of STEMI. Women more often have severe complications and a worse in-hospital prognosis.